Question
upstudy study bank question image url

QUESTION 7 7.1 Determine \( f^{\prime}(x) \) from first principles if \( f(x)=\frac{1}{x} \). 7.2 Determine: 7.2.1 \( \frac{d}{d x}\left(\sqrt{4 x^{6}}+\sqrt{2} \cdot x^{2}\right) \) 7.2.2 \( g^{\prime}(x) \) if \( g(x)=\frac{3 x^{4}-4 x^{2}+6}{x^{2}} \) (3) 7.3 The equation of the tangent to \( f(x)=3 x^{2}+b x+c \) at \( x=1 \) is given by \( y=9 x-9 \). Determine the values of \( b \) and \( c \). (4) [15]

Ask by Mills Kelly. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

7.1. \( f'(x) = -\frac{1}{x^2} \) 7.2.1. \( \frac{d}{dx} \left( \sqrt{4x^6} + \sqrt{2} \cdot x^2 \right) = 6x^2 + 2\sqrt{2}x \) (for \( x \geq 0 \)) 7.2.2. \( g'(x) = 6x - \frac{12}{x^3} \) 7.3. \( b = 3 \) and \( c = -6 \)

Solution

Below is the full solution with step‐by‐step reasoning. ───────────────────────────── Problem 7.1 ───────────────────────────── We wish to find f′(x) from first principles for   f(x) = 1/x. Using the definition of the derivative:   f′(x) = lim₍ₕ→0₎ [f(x + h) − f(x)] / h Step 1. Write the difference quotient:   f′(x) = lim₍ₕ→0₎ [(1/(x + h) − 1/x) / h]. Step 2. Combine the fractions inside the bracket:   1/(x+h) − 1/x = (x − (x+h)) / [x(x+h)] = −h / [x(x+h)]. Thus,   f′(x) = lim₍ₕ→0₎ [ (−h / (x(x+h))) / h ]. Step 3. Cancel h (as long as h ≠ 0):   f′(x) = lim₍ₕ→0₎ [−1 / (x(x+h))]. Step 4. Take the limit as h → 0:   f′(x) = −1 / (x·x) = −1/x². ───────────────────────────── Problem 7.2.1 ───────────────────────────── Determine the derivative of   f(x) = √(4x⁶) + √2 · x². Step 1. Rewrite √(4x⁶):   √(4x⁶) = √4 · √(x⁶) = 2|x³|. For many problems, the domain is assumed to be x ≥ 0 so that |x³| = x³. (If x can be negative, you must account for the absolute value; here we assume x ≥ 0.) Thus, assume x ≥ 0 and get:   f(x) = 2x³ + √2 · x². Step 2. Differentiate term-by-term:   d/dx (2x³) = 6x²,   d/dx (√2 · x²) = 2√2 x. The derivative is:   f′(x) = 6x² + 2√2 x. ───────────────────────────── Problem 7.2.2 ───────────────────────────── Find g′(x) for   g(x) = (3x⁴ − 4x² + 6) / x². Step 1. Divide each term in the numerator by x²:   g(x) = 3x² − 4 + 6/x². Step 2. Differentiate term-by-term:   d/dx (3x²) = 6x,   d/dx (−4) = 0,   d/dx (6/x²) = 6 · d/dx (x^(−2)) = 6(−2)x^(−3) = −12/x³. Thus,   g′(x) = 6x − 12/x³. ───────────────────────────── Problem 7.3 ───────────────────────────── The function is   f(x) = 3x² + bx + c, and the equation of the tangent at x = 1 is given as   y = 9x − 9. The tangent line must satisfy two conditions at x = 1: 1. It must pass through the point (1, f(1)). 2. Its slope must equal f′(1). Step 1: Use the point of tangency.   f(1) = 3(1)² + b(1) + c = 3 + b + c. The tangent line at x = 1 gives y = 9(1) − 9 = 0. Thus,   3 + b + c = 0  →  b + c = −3.                  (Equation 1) Step 2: Use the slope.   f′(x) = derivative of 3x² + bx + c = 6x + b. Then, at x = 1:   f′(1) = 6 + b. Since the slope of the tangent is 9, we have:   6 + b = 9  →  b = 3. Step 3: Substitute b = 3 into Equation 1:   3 + c = −3  →  c = −6. ───────────────────────────── Final Answers Summary ───────────────────────────── 7.1   f′(x) = −1/x². 7.2.1  d/dx [√(4x⁶) + √2·x²] = 6x² + 2√2 x      (for x ≥ 0). 7.2.2  g′(x) = 6x − 12/x³. 7.3   For f(x) = 3x² + bx + c with tangent y = 9x − 9 at x = 1, we have b = 3 and c = −6.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To find \( f^{\prime}(x) \) from first principles for \( f(x)=\frac{1}{x} \), we start with the definition of the derivative: \[ f^{\prime}(x) = \lim_{h \to 0} \frac{f(x+h) - f(x)}{h} = \lim_{h \to 0} \frac{\frac{1}{x+h} - \frac{1}{x}}{h} = \lim_{h \to 0} \frac{x - (x+h)}{h \cdot x(x+h)} = \lim_{h \to 0} \frac{-h}{h \cdot x(x+h)}. \] This simplifies to: \[ f^{\prime}(x) = \lim_{h \to 0} \frac{-1}{x(x+h)} = -\frac{1}{x^2}. \] In resolving \( \frac{d}{d x}\left(\sqrt{4 x^{6}}+\sqrt{2} \cdot x^{2}\right) \), we first simplify: \[ \sqrt{4 x^6} = 2x^{3}, \text{ so } f(x) = 2x^{3} + \sqrt{2}x^{2}. \] Now, using the power rule, we differentiate: \[ \frac{d}{dx}(2x^{3}) = 6x^{2}, \quad \frac{d}{dx}(\sqrt{2}x^{2}) = 2\sqrt{2}x. \] So, \[ \frac{d}{dx}\left(\sqrt{4x^{6}}+\sqrt{2} \cdot x^{2}\right) = 6x^{2} + 2\sqrt{2}x. \] For \( g^{\prime}(x) \) where \( g(x) = \frac{3x^4 - 4x^2 + 6}{x^2} \), we can use the quotient rule: \[ g^{\prime}(x) = \frac{(12x^3 - 8x)(x^{2}) - (3x^4 - 4x^2 + 6)(2x)}{(x^2)^2}. \] Simplifying gives: \[ g^{\prime}(x) = \frac{12x^5 - 8x^3 - 6x^2 + 8x^2 - 12x^4 + 8}{x^4} = \frac{(12x^5 - 12x^4) + 8 - 6x^2}{x^4}. \] Moving to the next point, for the tangent line to \( f(x) = 3x^{2} + b x + c \) at \( x = 1 \) being \( y = 9x - 9 \), we know the slope (derivative) at that point must equal 9: \[ f'(x) = 6 + b = 9 \implies b = 3. \] Now substituting \( x = 1 \): \[ f(1) = 3(1^2) + 3(1) + c = 6 + c = -9 \implies c = -15. \] Thus, \( b = 3 \) and \( c = -15 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy